Implementing Mobile HRV Biofeedback as Adjunctive Therapy During Inpatient Psychiatric Rehabilitation Facilitates Recovery of Depressive Symptoms and Enhances Autonomic Functioning Short-Term: A 1-Year Pre–Post-intervention Follow-Up Pilot Study - Tatschl, Josef M.; Hochfellner, Sigurd M.; Schwerdtfeger, Andreas R. (Frontiers in Neuroscience, 2020)
Objective New treatment options for depression are warranted, due to high recurrence rates. Recent research indicates benefits of heart rate variability biofeedback (HRVBF) on symptom recovery and autonomic functioning in depressed individuals. Slow-paced breathing-induced amplification of vagus nerve activity is the main element of HRVBF. Thus, the latter represents a safe and non-invasive complementary depression treatment. However, its efficacy in patients undergoing inpatient psychiatric rehabilitation receiving highly comprehensive treatments has not been evaluated. Methods Ninety-two inpatients were randomly assigned to an intervention group (IG) or control group (CG). While the latter received the standard treatment only, adjunctive HRVBF was provided to the IG over 5 weeks. Depression severity and heart rate variability (HRV) were assessed before (pre) and after 5 weeks (post). Moreover, 1-year follow-up depression scores were available for 30 participants. Results Although depression improved in both groups, the IG exhibited significantly larger improvements at post-assessment (ηp2 = 0.065) and significant increases in resting LF-HRV (d = 0.45) and cardiorespiratory coherence (d = 0.61). No significant effects for RMSSD, SDNN, HF-HRV, or HR were found (ps > 0.05). Additionally, the IG showed a medium- to large-sized reduction in resting respiratory rate from 13.2 to 9.8 breaths per minute (p < 0.001, d = 0.86), with the CG exhibiting only a small decrease from 13.5 to 12.4 (p = 0.49; d = 0.35). While the IG exhibited significantly lower depression scores at post-assessment (p = 0.042, d = 0.79), this effect decreased during follow-up (p = 0.195, d = 0.48). Conclusion HRVBF as adjuvant therapy during inpatient psychiatric rehabilitation facilitated depression recovery. Additionally, amplified LF-HRV as well as cardiorespiratory coherence at rest and a decrease in resting breathing frequency was observed in the HRVBF group. These findings emphasize HRVBF’s value as complementary therapy regardless of concurrent treatments. Moreover, these incremental benefits could serve as resource even after the actual training period. However, the additional antidepressant gains vanish during the long-term follow-up, indicating the need for more intense training or regular practice afterward, respectively. Thus, future studies are warranted to examine how the initial benefits of HRVBF during inpatient psychiatric rehabilitation can be preserved post discharge.